Wakamono Kotoba Dalam Situs Web Majalah Daring Numan.Tokyo - Ghifari, Muhammad Naufal; Suri, Intan; Aibonotika, Arza (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the most dominant type of wakamono kotoba formation in the latest wakamono kotoba 2023 on the numan.tokyo website. This study uses a descriptive qualitative method with library or documentation techniques as data collection techniques and content analysis techniques to obtain analysis results in the form of written descriptive explanations. The data was taken from the uploaded articles of new terms during 2023, with a total of 51 findings of new terms. After identification, 25 out of 51 data are wakamono kotoba with 9 different word formation processes, namely foreign language use, word truncation, word merging, verb derivation, adjective derivation, yomikae, initialization and word play with word truncation as the dominant. The findings show the most dominant process in the formation of wakamono kotoba 2023 of numan.tokyo online magazine is by word truncation, and provide insight into how these wakamono kotoba are formed.